Establishment of a novel engineering breeding technology for cytoplasmic male sterility - Na Xu; Dong Yu; Longhui Zhang; Tiankang Wang; Zhongxiao Hu; Quanqiang Lei; Yingxin Qiu; Zheming Yuan; Shufeng Song; Li Li (Crop Journal)
The three-line hybrid rice system, which relies on cytoplasmic male sterility (CMS), faces challenges in breeding efficiency. To address these challenges, we developed CMS engineering breeding technology (CEBT). First, we constructed a complementation vector containing the fertility restoration module Double Rf4-Rf20, sorting marker gene DsRed2, and pollen lethal gene ZmAA1, then transformed this into a CMS line. We obtained reproductive lines without alterations to main agronomic traits, which can produce engineering sterile lines (ESL) and reproductive line seeds at a 1:1 ratio by self-crossing. CEBT converts the traditional three-line system into an efficient ‘new two-line’ hybrid framework: the reproductive line is improved while simultaneously improving the ESL, which significantly shortens the breeding process for three-line hybrid rice.